Incremental Effect of Service Orientation, Perceptions of Organizational Politics, and Employee Engagement on Job Embeddedness in Hotels of North Cyprus - Teimouri, Reza Bahman (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
This research analyzes a reasonable model indicate that the rate of increase on job embeddedness as a result of service orientation in a low perceptions of organizational politics is higher compared to an organization with high perceptions of organizational politics. In addition, employee engagement has mediating effect on the relationship between service orientation and job embeddedness. Three hundred and seven employees with 47 manager groups were selected as samples 14 five-star hotels in Northern Cyprus for this study. The data were analyzed using the multi-level analysis following the hierarchical linear modeling considering the employees were nested in the departments. As hypothesized, the results demonstrated that the employee engagement partially mediates the effects of service orientation on job embeddedness. The results also indicated that interaction of service orientation and perceptions of organizational politics has negative influence on job embeddedness, which is an important signal to the hotels in the research context. Hotel managers must seek to adopt and focus on an excellent service orientation for training. Furthermore, new procedures and policies should be devised by the management of the lower star hotels within Northern Cyprus i.e. five-star hotels, which would aid in minimizing the possible effects of political decisions likewise adopting a more professional approach in the various aspects of their operations. In addition, there are very limited empirical researches have been conducted in the field of human resource and hospitality management on the links between employee engagements, perceptions of organizational politics, job embeddedness and service orientation. Hence, the significance of this study as it aims to fill the gap by examining the mediating and moderating roles of employee engagement and perceptions of organizational politics using a multi-level model for five-star hotel industry in Northern Cyprus is necessary. Keywords: Employees, Employee engagement, Job embeddedness, Cyprus, Perceptions of organizational politics, Service orientation.

ÖZ: Bu araştırma, hizmet yöneliminin iş uyumu üzerindeki etkisini artıran ve örgütsel algıların, çalışanların otel organizasyonundaki işe uyumu konusundaki zorunluluğunu geliştirebilecek en uygun modeli analiz etmektedir. Ayrıca, çalışan iş uyumu ve hizmet yönelimi arasındaki ilişki dolaylı etki aracılığıyla da incelenmektedir. Bu çalışma için Kuzey Kıbrıs'taki 14 adet beş yıldızlı otelden, 47 yönetici grubuyla 307 çalışan örneklem olarak seçilmiştir. Veriler, çalışanların bir araya getirilmiş oldukları departmanlar göz önüne alınarak, hiyerarşik lineer modellemeyi takip eden çoklu seviye analizi ile analiz edilmiştir. Varsayıldığı üzere, sonuçlar özellikle, örgütsel politika algılarının düşük etkileri olduğu otellerin departmanlarında etkileyici bir çalışan bağlılığı için; hizmet yönelimi etkilerinin iş uyumuna kısmen aracılık ettiğini göstermiştir. Hiç şüphesiz ki, örgütsel politika algıları etkin çalışan bağlılığının olumsuz bir parçası olduğunda, bu personellerin yüksek iş uyumuna neden olmaktadır. Otel yöneticileri, eğitim için son derece iyi bir hizmet yönelimini benimsemeli ve odaklanmalıdır. Ayrıca, Kuzey Kıbrıs'ta bulunan ve beş yıldızlı olmayan diğer otel yönetimleri ile de yeni usuller ve politikalar geliştirilmelidir. Örneğin, politik kararların olası etkilerini en aza indirgemeye yardımcı olan beş yıldızlı oteller, benzer şekilde, faaliyetlerinin çeşitli yönlerinde daha profesyonel bir yaklaşım benimsemektedir. Ayrıca, insan kaynakları ve otel yönetimi alanında; çalışan bağlılığı, örgütsel politika algıları, işe uyumu ve hizmet yönelimi arasındaki ilişkileri inceleyen çok sınırlı deneysel araştırmalar yapılmıştır. Bu nedenle, çalışmanın önemi, Kuzey Kıbrıs'taki beş yıldızlı otel endüstrisi için çoklu seviye analizi kullanılarak, çalışan bağlılığının ve örgütsel politika algılarının aracı ve düzenleyici rolleri yönündeki boşluğu doldurmaktır. Anahtar Kelimeler: Çalışanlar, Çalışanların Bağlılığı, İş Uyumu, Kıbrıs, Örgütsel Politika Algıları, Hizmet Yönelimi.
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2018. Co-Supervisor: Hüseyin Araslı and Supervisor: Prof. Dr. Hasan Kılıç.
Keywords: Tourism; Organizational behavior--Psychology, Industrial--Organizational effectiveness; Tourism--Hotels--Cyprus, North; Work Attitudes--Job Satisfaction itizenship--Organizational Climate; Human Resources Management; Employees; Employee engagement; Job embeddedness; Cyprus; Perceptions of organizational politics; Service orientation